SISTEM INFORMASI GEOGRAFIS (SIG) DAERAH RAWAN BANJIR DI KOTA BENGKULU MENGGUNAKAN ARCVIEW - Rahma Wayan Lestari; Indra Kanedi; Yode Arliando (UNIVED Press, 2016)
The purpose of this research is to create a geographic information system Bengkulu city flood-prone areas using ArcView. Apply the knowledge obtained during the lecture, especially relating to the development of Geographic Information Systems. To be able to produce a system that is accurate and useful information for the community. Where the research was conducted in the city of Bengkulu BASARNAS. Bengkulu BASARNAS office specializing in Search and Rescue (SAR), is the body that manage the flood of data that is still done manually, using Microsoft Word and Microsoft Excel. Thus experiencing problems in delivering information directly to the office because the SAR agencies require a long time.Keywords: Geographic Information System, Flood Prone Area